The Revision of the Proper Law of the Discalced Carmelites in Today’s Times - KIWIOR , WIESŁAW (Prawo Kanoniczne, 2019)
From the legislative procedure, used by the Order in the years 1968-1986, one can choose elements that are fruitful for the revision and updating of the norms of the proper law of the Discalced Carmelites in today's time. The research and discernment required by this work should - depending on the case - encourage or strengthen or turn into a theological and meditative reading of the Constitutions in order to deepen one's vocational identity in the Church and - as the text of the Carmelite-Theresian formula for religious profession says - to live faithfully in union with the Virgin Mary in obedience to Jesus Christ, to give oneself wholeheartedly to the religious family initiated by the Founders, to devote oneself to perennial prayer and to the apostolic service of the Church, to attain perfect charity and to glorify the Most Holy Trinity for all eternity. A greater consideration for the Rule and the Constitutions - as Saint John Paul II reminds us - will offer religious "a sure criterion for seeking appropriate forms of witness that know how to respond to the needs of the moment without departing from the initial inspiration". It will help them - on a personal, community and institutional level - in the continuous renewal of their religious life and in relaunching a dynamic, creative and fraternal fidelity.